2002
DOI: 10.1515/cclm.2002.108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Commutability of Control Materials

Abstract: The commutability of 13 control materials was evaluated by performing parallel measurements on two different analysers: a Synchron CX-5 Delta from Beckman-Coulter and a Vitros 950 from Ortho-Clinical Diagnostics. Twenty three clinical chemistry analytes (substrates, electrolytes and enzymatic activities) were determined in plasma from 15 different patients in order to define intermethod relationship for each analyte. The relationship observed for each control material was compared to those obtained for patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
8
0
2
Order By: Relevance
“…This is expected as the measurement principles differ significantly in the first case and are very similar in the second. 3 The wide range of dispersions found may reflect the variations in concentrations of different proteins with their individual interferences in different assays and point to the fact that measurement of albumin in plasma or serum is complicated and may need improvements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is expected as the measurement principles differ significantly in the first case and are very similar in the second. 3 The wide range of dispersions found may reflect the variations in concentrations of different proteins with their individual interferences in different assays and point to the fact that measurement of albumin in plasma or serum is complicated and may need improvements.…”
Section: Discussionmentioning
confidence: 99%
“…6 In addition, it has been shown that the propensity to non-commutability of processed materials is greater where the analytical method principles of the methods being used in the commutability study differed significantly. 3 Currently available methods for the measurement of albumin in serum or plasma vary in their principles of measurement, ranging from dye-binding methods to immunoturbidimetric and immunonephelometric methods. All these methods have been shown to demonstrate significant metrological differences.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys published in this journal have concluded that both national and international quality control programs are useful for indicating the intrinsic quality of the quantities used in the clinical laboratory [ 24 ]. Problems with quality control materials and the lack of communicability have also been discussed [ 25 ]. Commutability depends both on the analyte being tested and the control material.…”
Section: The Impact Of Clinical Chemistry and Laboratory Medicine On mentioning
confidence: 99%
“…Since then, commutable reference materials have been established for several analytes, including glucose, triglycerides, and others (14,15 ). Although the commutability concept has been emphasized in the area of clinical chemistry, it has not yet been applied in the area of nucleic acid testing.…”
Section: © 2009 American Association For Clinical Chemistrymentioning
confidence: 99%